A randomized, controlled crossover trial of ondansetron in patients with primary biliary cirrhosis and fatigue - Theal, Jeremy J.; Toosi, Mohssen N.; Girlan, Larisa; Heslegrave, Ronald J.; Huet, Pierre‐Michel; Burak, Kelly W.; Swain, Mark; Tomlinson, George A.; Heathcote, E. Jenny (Hepatology (Baltimore, Md.), 2005)
Fatigue is common in primary biliary cirrhosis (PBC). Altered central serotonergic neurotransmission may be involved in its pathogenesis. This multicenter, randomized, double-blind, placebo-controlled, crossover trial evaluated the efficacy of ondansetron, a selective 5-HT3 receptor subtype antagonist, for treating fatigue in PBC. A crossover design was chosen, allowing subjects to serve as their own controls-appropriate to evaluate fatigue, a subjective symptom. Sixty patients with clinically stable PBC, a Fatigue Severity Score (FSS) > 4, and no other identifiable cause for fatigue were enrolled. Subjects were randomized to receive ondansetron (4 mg) or placebo orally 3 times daily for 4 weeks (period 1). Subjects then crossed over, after a minimum 1-week washout period, for a further 4 weeks of ondansetron or placebo (period 2). Fatigue was measured at the beginning and end of each period by using the FSS and Fatigue Impact Scale (FIS). Six patients withdrew; the remaining 54 subjects had a mean baseline FSS of 5.55 (+/-0.1). Response to study medication in period 1 versus period 2 was not uniform; thus, it was necessary to analyze the trial periods separately. In period 1, there was no significant additional fatigue reduction on ondansetron over placebo. During period 2, FSS and FIS decreased significantly on ondansetron versus placebo (P = .001). However, period 2 results were invalidated because drug side effects unblinded subjects (constipation affected 63.0% of patients taking ondansetron, versus 13.3% on placebo). In conclusion, ondansetron administration did not confer clinically significant fatigue reduction when compared with placebo in our study population.